Multidisciplinary Approach to Patients With Metastatic Spinal Cord Compression: A Diagnostic Therapeutic Algorithm to Improve the Neurological Outcome - Rispoli, Rossella; Reverberi, Chiara; Targato, Giada; D’Agostini, Serena; Fasola, Gianpiero; Trovò, Marco; Calci, Mario; Fanin, Renato; Cappelletto, Barbara (Frontiers in Oncology, 2022)
Introduction The morbidity associated with metastatic spinal disease is significant because of spinal cord and/or nerve root compression. The purpose of this paper is to define a diagnostic-therapeutic path for patients with vertebral metastases and build an algorithm with the aim of reducing the devastating consequences of spinal cord compression. Materials and methods The institution where the algorithm was built is a primary care center. The team formed to forge the diagnostic-therapeutic path consists of the emergency room (ER) physician, the spine surgeon, the neuroradiologist, the radiation oncologist, and the oncologist. The ER doctor or oncologist is assigned to recognize the symptoms and signs of a metastatic spinal cord compression and must trigger the next steps of the flow-chart. Upon referral by the ER,or oncologist, the spine surgeon takes charge of the patient and, based on a detailed collection of anamnestic data and the neurological examination, defines the appropriate timing for magnetic resonance imaging (MRI) in collaboration with the neuroradiologist. From the MRI outcome, the spine surgeon and the radiation oncologist consult each other to define further therapeutic alternatives. If indicated, surgical treatment should precede radiation therapy. The oncologist gets involved after surgery for systemic therapy. Discussion Patients with a history of malignancy can present to the ER or to the oncology department with symptoms that must be correctly framed in the context of a metastatic involvement. Even when there is no previous cancer history, the patient's pain characteristics and clinical signs must be interpreted to yield the correct diagnosis of vertebral metastasis with incipient or current spinal cord compression. Early surgical or radiation therapy treatment gives the best hope for preventing the worsening, or even improving, the deficits. Conclusions Metastatic spinal cord compression can cause neurological deficits compromising quality of life. Treatment strategies should be planned comprehensively. A multidisciplinary approach and the application of the proposed algorithm is of paramount importance to optimize the outcomes of these patients.